Implementation of Social Media Marketing, Brand Trust, Brand Satisfaction in Increasing Consumer Loyalty to Skincare Products - Sidabutar, Henny; Febriansyah Febriansyah (Dinasti Review, 2024)
Social media also helps in the dissemination of promotional information and product usage experiences. The development of the beauty and skincare industry has become significant due to the awareness of the importance of maintaining healthy skin, especially in urban areas with high levels of pollution. The use of skincare products has become an inevitable trend, both among women and men, including children who are starting puberty. Price factors, promotions, product quality, and recommendations from close people greatly influence the decision to purchase skincare products. The beauty industry in Indonesia, which is the third largest market in Asia, shows great potential with increasing export levels. Awareness of skincare not only provides physical benefits but also positive psychological impacts, such as increasing self-confidence and providing relaxation. Thus, skincare practices have become an important part of a healthy and sustainable lifestyle.